A call for unity in DEIJ efforts using a proposed framework for Education, Recruitment, Retainment, Research, and Active outreach (ERA) for genetic counselors in the United States. Issue 3 (10th January 2022) - Mercado, Joanna; Lawrence, Janette Z.; Moore, Michelle; Neogi, Arpita; Vig, Hetal
Abstract: Genetic counselors, like many other healthcare providers, play a vital role in genomic health care. As a profession, we, along with our colleagues and students, have recognized the need to improve and incorporate diversity, equity, inclusion, and justice (DEIJ) within our daily ways of practice to help create access to genomic technologies. In order to create systemic change and focus on unity, open communication, and transparency, we introduce a suggested framework called ERA (Education, Recruitment, Retainment, Research, and Active Outreach). This framework would benefit a genetic counselor throughout various stages of their career, from student to practicing genetic counselor, and can be broadly applied to all specialties of genomic medicine. Different iterations of DEIJ efforts have arisen in the National Society of Genetic Counselors (NSGC), from the D&I (Diversity and Inclusion) Task Force to the J.E.D.I (justice, equity, diversity, and inclusion) committee. The lack of recorded history of these previous efforts and the lack of communication between current DEIJ organizations is one of the many reasons the ERA framework demands unity and transparency to achieve sustainable positive change. Genetic counselors must unite and work collaboratively to conduct and promote DEIJ efforts, so the benefits of genomic medicine can be realized by all.